2022
DOI: 10.3390/toxins14110738
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Multiple GWAS Results Identifies Metabolic Pathways Associated with Resistance to A. flavus Infection and Aflatoxin Accumulation in Maize

Abstract: Aflatoxins are carcinogenic secondary metabolites produced by several species of Aspergillus, including Aspergillus flavus, an important ear rot pathogen in maize. Most commercial corn hybrids are susceptible to infection by A. flavus, and aflatoxin contaminated grain causes economic damage to farmers. The creation of inbred lines resistant to Aspergillus fungal infection or the accumulation of aflatoxins would be aided by knowing the pertinent alleles and metabolites associated with resistance in corn lines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…The GWAS output was run through the Pathway Analysis Study Tool (PAST) (Thrash et al 2020 ) on the MaizeGDB website ( https://www.maizegdb.org/past ), as described in Tang et al ( 2015 ) and Warburton et al ( 2022 ). The data used in PAST included the p-values (the significant SNP-trait association values); R 2 (proportion of the explained phenotypic variation), effect values along with the calculated LD values for D’ and R 2 , and the p-value between each SNP marker and its closest neighboring SNPs (Tang et al 2015 ; Warburton et al 2022 ). SNPs were then assigned to genes, and the functions of candidate genes were assessed by examining the pathways in which the encoded enzymes were involved (Warburton et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GWAS output was run through the Pathway Analysis Study Tool (PAST) (Thrash et al 2020 ) on the MaizeGDB website ( https://www.maizegdb.org/past ), as described in Tang et al ( 2015 ) and Warburton et al ( 2022 ). The data used in PAST included the p-values (the significant SNP-trait association values); R 2 (proportion of the explained phenotypic variation), effect values along with the calculated LD values for D’ and R 2 , and the p-value between each SNP marker and its closest neighboring SNPs (Tang et al 2015 ; Warburton et al 2022 ). SNPs were then assigned to genes, and the functions of candidate genes were assessed by examining the pathways in which the encoded enzymes were involved (Warburton et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to identifying genomic regions and genes involved in disease resistance, GWASs also assist in identifying resistance pathways and associated genes. Metabolic pathway analysis focuses on the combined effects of many genes clustered together because of their shared biological functions (Tang et al 2015 ; Warburton et al 2022 ). This type of research complements the study of the most significant marker-trait associations in addition to giving clues on the genetic basis of specific traits (Tang et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, no aflatoxin mapping was made, such that forecasting of the aflatoxin content could not be concluded. Another paper [169] reported that most commercial hybrids are susceptible to A. flavus and aflatoxin contamination. Through a multiple QTL analysis, several dozen QTLs with small effect were identified.…”
Section: Aspergillus Ear Rotmentioning
confidence: 99%
“…Accumulating disease-resistant QTL can enhance plant resistance, underscoring the importance of identifying additional resistance QTL to further enhance maize resistance to common rust. [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%